Diminished vagal tone is a predictive biomarker of necrotizing enterocolitis‐risk in preterm infants. Issue 6 (11th April 2014) - Doheny, K. K.; Palmer, C.; Browning, K. N.; Jairath, P.; Liao, D.; He, F.; Travagli, R. A.
Abstract Background Necrotizing enterocolitis (NEC) is an acute neonatal inflammatory disease which may lead to intestinal necrosis, multisystem failure, and death. Currently, NEC is diagnosed by a combination of laboratory and radiographic tests conducted a posteriori i.e., when NEC is already clinically significant. Given the acute onset and rapid progression of NEC, a non‐invasive biomarker that allows early detection of patients at risk is required as a matter of urgency. We evaluated whether the high frequency (HF) component of heart rate variability (HRV), a measure of vagal efferent tonic cholinergic activity may be used as a predictive biomarker for NEC‐risk before the onset of clinical disease. Methods In this prospective study, stable preterm (gestational age 28–35 weeks) infants had HRV power spectra analyzed from surface electrocardiogram waveforms taken at rest on day 5–8 of life. We used regression modeling to determine the utility of HF‐HRV in predicting NEC. Key Results HF‐HRV power was 21.5 ± 2.7 and 3.9 ± 0.81 ms2 in infants that remained healthy and those that later developed stage 2+ NEC, respectively (p < 0.001). Nine of 70 enrolled infants developed NEC. The ROC discriminated a HF‐HRV value of 4.68 ms2 predictive for developing NEC with a sensitivity and specificity of 89% and 87%, and positive and negative predictive value of 50% and 98%, respectively. With predictive regression modeling, the risk (odds ratio) of developing NEC was 10 per every one SD decrease in HF‐HRV. Conclusions & Inferences Our preliminary data indicate that HF‐HRV may serve as a potential, non‐invasive predictive biomarker of NEC‐risk in NICU infants.